Analisis Pemahaman Pengurus dan Anggota Koperasi dalam Implementasi Manajemen Ritel - Yulhendri - Yulhendri; Wiwik Gurnita; Annur Fitri Hayati; Elvi Rahmi; Tri Kurniawati (Universitas Negeri Padang, 2022)
Management and members need to increase their knowledge and skills regarding the form of business run by cooperatives so that later the goals of the cooperative can be achieved. This research uses descriptive method. With a comparative approach. This research is intended to test whether there are differences in the understanding of cooperative management and members in the implementation of retail management in the Serumpun Melati Putih Cooperative and the Pulau Harapan Cooperative before and after the training. The research respondents were the administrators and members of the Serumpun Melati Putih Cooperative and the Pulau Harapan Cooperative which amounted to 14 people, the data was collected in July 2022 with the data collection technique in the form of a test. The test given is in the form of questions related to understanding of retail management. The prerequisite test analysis uses a normality test. The data is processed by using paired sample t test. The results of the study indicate that there are differences in the understanding of the administrators and members of the cooperative regarding the implementation of retail management before and after the implementation of the training provide